As intenções comportamentais dos agricultores familiares na tomada de decisão pela diversificação ou especialização da produção - Hansel , Tiago Fernando (2022)
This thesis aims to analyze the behavioral intentions of family farmers through the Theory of Planned Behavior in decision-making for diversification or specialization of production. The delimitation of this objective was made in order to fill an identified research gap, since no studies identical or similar to the focus of this thesis were detected. To meet the proposed objective, applied and exploratory research was used, with bibliographic and field research procedures, with a qualitative approach, the object of study being family farmers with diversified and specialized production, with the field of study of 40 family farmers from the 20 municipalities covered by the Paraná Rural Development Institute of the Toledo Regional, in the west of Paraná. As a technique for data collection, interviews were carried out with a defined route and a semi-structured interview script. Data were recorded descriptively, with the aim of understanding the characteristics of the investigated samples. Tabulation and content analysis were performed using the MAXQDA software. The results indicate that there isn’t intention on the part of family farmers of diversified productive character to migrate to specialization, on the other hand, a small portion of farmers with specialized production showed an intention to diversify their production, but the volume is low compared to specialized ones, who has no intention of changing their productive style. In addition, it was identified that within the constructs of the Theory of Planned Behavior, perceived behavioral control is the most significant and expressive in the formation of the intention of these family farmers, followed by the construct of attitude and subjective norm, these two being less expressive than the perceived behavioral control construct, but similar between them, but significant for the formation of the behavioral intention of these family farmers. Therefore, it’s concluded that the Theory of Planned Behavior is effective to measure the intention of family farmers in decision-making for the continuation or change of their productive style. It’s also concluded that there isn’t intention on the part of diversified family farmers to change their production style and that there is, with low expressiveness, an intention to change the production format on the part of specialized farmers. This study can contribute to the formulation of strategies and public policies aimed at rural development and sustainability in small rural properties.